2013
DOI: 10.1371/journal.pone.0057885
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of Wheat Stripe Rust Resistance Gene Yr26 Based on Collinearity of Wheat with Brachypodium distachyon and Rice

Abstract: The Yr26 gene, conferring resistance to all currently important races of Puccinia striiformis f. sp. tritici (Pst) in China, was previously mapped to wheat chromosome deletion bin C-1BL-6-0.32 with low-density markers. In this study, collinearity of wheat to Brachypodium distachyon and rice was used to develop markers to saturate the chromosomal region containing the Yr26 locus, and a total of 2,341 F2 plants and 551 F2∶3 progenies derived from Avocet S×92R137 were used to develop a fine map of Yr26. Wheat exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 37 publications
1
33
1
Order By: Relevance
“…Thus, Brachypodium is more closely related to wheat than rice based on DNA sequence similarities in the genomic regions on the short arms of these three collinear chromosomes. These results are consistent with the observations reported in the previous studies (Catalan and Olmstead 2000;Draper et al 2001;Foote et al 2004;the International Brachypodium Initiative 2010;Zhang et al 2013). However, higher collinearity between wheat and rice than between wheat and Brachypodium has been observed in specific genomic regions (Faris et al 2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, Brachypodium is more closely related to wheat than rice based on DNA sequence similarities in the genomic regions on the short arms of these three collinear chromosomes. These results are consistent with the observations reported in the previous studies (Catalan and Olmstead 2000;Draper et al 2001;Foote et al 2004;the International Brachypodium Initiative 2010;Zhang et al 2013). However, higher collinearity between wheat and rice than between wheat and Brachypodium has been observed in specific genomic regions (Faris et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…However, higher collinearity between wheat and rice than between wheat and Brachypodium has been observed in specific genomic regions (Faris et al 2008). To date, many genes in wheat have been well characterized through comparative analysis with rice and Brachypodium genomic sequences (Liu et al 2003(Liu et al , 2006Bossolini et al 2007;Faris et al 2008;Somyong et al 2011;Zhang et al 2013). Comparative analysis of the Qfhs.ndsu-3AS QTL and nearby regions on 3AS tremendously enhanced genetic as well as physical mapping of the region in this study.…”
Section: Discussionmentioning
confidence: 97%
“…1Á92 Mb syntenic region in brachypodium harbours two RGAs. Zhang et al (2013) Phragmites spp. ), Stagonospora paspali (NH: bahiagrass; Paspalum notatum) and Stagonospora tainanensis (NH: sugarcane).…”
Section: Silvar Et Al (2012)mentioning
confidence: 99%
“…Nevertheless, many studies have reported poor levels of micro-colinearity between wheat and rice because of inversions, deletions, duplications, and other rearrangements [6], [7], [48], [63]. The isolation of the wheat disease resistance genes Lr10 , Lr21 and Pm3 has also shown that wheat and rice have very limited colinearity in the relevant chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%